Who feels scared? a book about being afraid - Graves, Sue; Guicciardini, Desideria (London Franklin watts, 2014)
Jack is having a sleepover at his house. But the boys hear noises and they get very scared! Jack's big sister Ellie says she gets scared sometimes as well. Perhaps Dad can make them all feel better?
Education
Keywords: Educational psychology